A Guinea Pig Model of Airway Smooth Muscle Hyperreactivity Induced by Chronic Allergic Lung Inflammation: Contribution of Epithelium and Oxidative Stress - Vasconcelos, Luiz Henrique César; Silva, Maria da Conceição Correia; Costa, Alana Cristina; Oliveira, Giuliana Amanda de; Souza, Iara Leão Luna de; Queiroga, Fernando Ramos; Araujo, Layanne Cabral da Cunha; Cardoso, Glêbia Alexa; Righetti, Renato Fraga; Silva, Alexandre Sérgio; da Silva, Patrícia Mirella; Carvalho, Carla Roberta de Oliveira; et al. (Frontiers in Pharmacology, 2019)
Asthma is a heterogeneous disease of the airways characterized by chronic inflammation associated with bronchial and smooth muscle hyperresponsiveness. Currently, different murine models for the study of asthma show a poor bronchial hyperresponsiveness due to the scarce smooth muscle and large airways, failing in reproducing smooth muscle hyperreactivity. Thus, we aimed to standardize a guinea pig model of chronic allergic lung inflammation mimicking airway smooth muscle hyperreactivity observed in asthmatics (Asth). Animals were randomly divided into control group (Ctrl), which received saline (0.9% NaCl), and Asth group, subjected to in vivo sensitization with ovalbumin (OVA) nebulization. Morphological analysis was performed by hematoxylin eosin staining. Bronchial hyperresponsiveness was evaluated by nebulization time in the fifth, sixth and seventh inhalations (NT5 7) and tracheal isometric contractions were assessed by force transducer. Total antioxidant capacity was measured by the 2,2 diphenyl 1 picrylhydrazyl (DPPH) method and protein expression by Western blot. Histologically, the Asth group developed peribronchial cellular infiltrate, epithelial hyperplasia and smooth muscle thickening. After the fourth nebulization, Asth developed bronchial hyperreactivity. The trachea from Asth contracted after in vitro stimulation with OVA, differing from Ctrl, which did not respond. Additionally, airway smooth muscle hyperreactivity to carbachol and histamine was observed in Asth, only in intact epithelium preparations, but not to KCl, and this effect was associated with an augmented production of reactive oxygen species. Moreover, lung inflammation impaired the relaxant potency of isoproterenol, only in intact epithelium preparations, without interfering with nifedipine, and it was found to be produced by transforming growth factor β negative modulation of β adrenergic receptors and, furthermore, the big-conductance Ca2+ sensitive K+ channels. Also, these effects were associated with increased levels of phosphatidylinositol 3 kinases but not extracellular signal regulated kinases 1/2 or phosphorylation, and augmented α actin content as well, explaining the increased smooth muscle mass. Furthermore, pulmonary antioxidant capacity was impaired in Asth. Therefore, we developed a standardized and easy-to-use, reproducible guinea pig model of lung inflammation that mimics airway smooth muscle hypercontractility, facilitating the investigation of the mechanisms of bronchial hyperresponsiveness in asthma and new therapeutic alternatives.